2014
DOI: 10.1016/j.jcin.2014.04.013
|View full text |Cite
|
Sign up to set email alerts
|

Radiation Dose Benchmarks During Cardiac Catheterization for Congenital Heart Disease in the United States

Abstract: This study presents age-stratified radiation dose values for 6 common congenital heart interventional catheterization procedures. Fluoroscopy time alone is not an adequate measure for monitoring radiation exposure. These values will be used as baseline for measuring the effectiveness of future quality improvement activities by the Congenital Cardiac Catheterization Project on Outcomes collaborative.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
25
3
7

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(38 citation statements)
references
References 34 publications
3
25
3
7
Order By: Relevance
“…The reported P KA figures are high but compatible with those reported by Verghese et al, 16 Glatz et al 31 and Ghelani et al, 34 although the majority of analysis is focussed on P KA normalized by mass. These P KA /kg figures are on average around four times higher than the recent era figures in the present study, around twice as high as those reported by Onnasch et al 12 but lower than the figure quoted by Chida et al 9 The authors recommend the use of P KA /kg as a standardized measure of paediatric cardiac catheterization doses.…”
Section: 4supporting
confidence: 89%
“…The reported P KA figures are high but compatible with those reported by Verghese et al, 16 Glatz et al 31 and Ghelani et al, 34 although the majority of analysis is focussed on P KA normalized by mass. These P KA /kg figures are on average around four times higher than the recent era figures in the present study, around twice as high as those reported by Onnasch et al 12 but lower than the figure quoted by Chida et al 9 The authors recommend the use of P KA /kg as a standardized measure of paediatric cardiac catheterization doses.…”
Section: 4supporting
confidence: 89%
“…With the Congenital Cardiac Catheterization Outcomes Project – Quality Improvement C3PO‐QI initiative, increased operator experience, and shorter procedure times, the amount of radiation to which patients are exposed has decreased over time. The radiation exposure for total air kerma and dose area product is lower than the ones reported previously by Ghelani et al . The lowest dose exposure occurs during pulmonary valvuloplasty and the highest during transcatheter pulmonary valve implantation.…”
contrasting
confidence: 55%
“…However, the variation in radiation exposure amongst centers suggests that further initiatives towards minimizing radiation dose in children to “as low as reasonably achievable” (the ALARA principle) and standardization of practice are warranted 29 . Comparisons between centers also highlight the inadequacy of fluoroscopy time alone as a metric of radiation dose estimate because of differences in programmed fluoroscopy modes, pulse rates, and cine acquisition frame rates 32 , 33 . Instead, recognition and comparison of actual radiation energy exposure such as dose area product and air kerma in relation to procedure types are more appropriate.…”
Section: Radiation Safetymentioning
confidence: 99%